SHALL WE LET THEM DIE? POSTWAR EVANGELICALISM AND GLOBAL SOCIAL MINISTRY: THE EARLY YEARS OF WORLD RELIEF, 1944-1950. - Mullin, Miles S. (Fides et historia, 2014)
The article discusses the founding years of the charitable organization World Relief, from 1944 to 1950 as the World Relief Commission (WRC) of the National Association of Evangelicals (NAE). Topics include the formation of the NAE's War Relief Commission (WRC) in the context of U.S. neo-evangelicalism, the WRC's assistance of postwar refugees in Europe following World War II, and the role of social ministry in the neo-evangelical movement.